Peri-Implantitis: A New Definition Proposal Based on Unnatural Spatial Arrangement and Late Mechanical Coupling between Two Cortical Bone Layers during Osseointegration Phase Part II - Stefan Ihde; Antonina Ihde; Olga Sipic; Łukasz Pałka (Applied Sciences, 2022)
To date, the term peri-implantitis has been mostly associated with bacterial or foreign body reaction as primary factors of its development. Because of this, researchers’ and clinicians’ attention regarding treatment possibilities were directed into the solutions on the basis of surface modifications, debridement, and antibiotics. After years of clinical observations and poor results in treatment of peri-implantitis, a new proposal of this condition is presented, shifting our way of thinking regarding bone and implant interactions. In the second part of the paper presenting a new definition of peri-implantitis, we focused on a biological explanation of the bone behavior at the bone–implant interface. The main conclusion is that PI is not an “infectious disease”, but rather the result of natural changes of the bone’s morphology in response to implant such as a decrease in convexity of the outer surface of the bone and subsequently a decrease in concavity of the inner bone.